PATENT RIGHT TRANSFER THROUGH WAQF: WHAT ARE THE REQUIREMENTS? - Praja, Chrisna Bagus Edhita; Mulyadi, Mulyadi; Riswandi, Budi Agus; Arifah, Kuni Nasihatun (Yustisia, 2018)
This study aims to examine and identify criteria for patents that can be used as waqf assets. Patents are very potential as waqf asset because of a large number of patent holders in Indonesia with the requirements of productive waqf. Patents are a type of Intellectual Property with the provision of a specified period and are still a debate related to the period of waqf which is always a pro and contradiction, some scholars consider waqf property to be forever but in the waqf law is allowed a waqf property with a specified period. This research method uses a normative legal research method with a Law approach and concept approach as well as secondary data review. The Act used is the Patent Law and the Waqf Act. The results show that the patent that can be used as an waqf asset refers to the provision of waqf property which includes (1) legal ownership of the patent owner and evidenced by a patent certificate (2) is not controversial which means not in a legal dispute until in Kracht van gewijsde or not in internal conflicts for patents owned by several inventors (3) have economic value and use value so that it can benefit the community. Patents can be used as an waqf asset because in the Waqf Law it is explained that the waqf property may be for a specified period. The period in the patent waqf in the deed of the waqf pledge must be adjusted to the period of patent protection.